Mediterranean Tomato‐Based Sofrito Sauce Improves Fibroblast Growth Factor 21 (FGF21) Signaling in White Adipose Tissue of Obese ZUCKER Rats. Issue 4 (30th January 2018) - Sandoval, Viviana; Rodríguez‐Rodríguez, Rosalía; Martínez‐Garza, Úrsula; Rosell‐Cardona, Cristina; Lamuela‐Raventós, Rosa M.; Marrero, Pedro F.; Haro, Diego; Relat, Joana
Abstract : Scope: Obesity is a fibroblast growth factor 21 (FGF21)‐resistant state. Since FGF21 production and signaling are regulated by some bioactive dietary compounds, we analyze the impact of Mediterranean tomato‐based sofrito sauce on: (i) the FGF21 expression and signaling in visceral white adipose tissue (vWAT), and (ii) the insulin sensitivity of obese Zucker rats (OZR). Methods and results: OZR are fed with a sofrito ‐supplemented diet or control diet. Insulin sensitivity and FGF21 signaling are determined. We observed that sofrito is able to improve the responsiveness to both hormones in obese rats. Sofrito ‐supplemented diet increases FGF21 signaling in vWAT by inducing the expression of the FGF receptors (FGFR1 and FGFR4) that promotes the expression of canonical target genes, like Egr‐1, c‐Fos and uncoupling protein 1 (Ucp1). Conclusions: A sofrito‐ supplemented diet improves insulin and FGF21 sensitivity in OZR, explaining part of sofrito 's healthy effects on glucose metabolism. In addition, induction of UCP1 and the unchanged body weight despite the hyperphagic behavior of the sofrito ‐fed rats suggests that the increase in FGF21 signaling correlates with an increase in energy expenditure (EE). Further studies in humans may help to understand whether sofrito consumption increases the EE in obese individuals. Abstract : Since FGF21 signaling is regulated by some bioactive dietary compounds, the impact of Mediterranean tomato‐based sofrito sauce on the FGF21 signaling of obese Zucker rats (OZR) was analyzed. A sofrito‐ supplemented diet is shown to increase the expression of FGF21 receptors and its target genes. The induction of UCP1 with an unchanged body weight suggests that the improvement in FGF21 signaling correlates with an increase in energy expenditure.